PERANCANGAN KEMASAN KERUPUK TALAS DUA PUTRA DI NAGARI AIA TABIK, KECAMATAN BASO, KABUPATEN AGAM - RAHMAT HIDAYAT, Dr. Budiwirman, M.Pd, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
“Kerupuk Talas Dua Putra" is one of the culinary delights that exist in the Nagari Aia Tabik, Kecamatan Baso, Agam, established in 2005 with owner is Rina Rimanti. The weakness of this product are on the packaging wrapped in clear plastic, packaging is less attractive to consumers because of the impression of the ordinary.The design of this package consists of a box, plastic, and cardboard. Layout product logos, illustrations “Kerupuk Talas Dua Putra" with the headline "Nan sabana Rapuah", the tagline "cemilan Khas Sumatera Barat" will reinforce the view and information about the product packaging delivered invitation.Proper design method is the SWOT analysis for the redesign existing packaging design, with a balance of strengths, weaknesses, opportunities, and threats that a comparison between the new designs, old designs and products of competitors. Packaging design as a means of communication can be interpreted that the packaging design not only as a wrap or cover an item or group of items, but provide information that is clear andcomplete for the content or the content of a product, ideally when thepackaging design is able to provide information to consumers valuewill better to avoid consumer confusion.Keywords: Design, Packaging, Kerupuk Talas